Family intervention model for changes in family behavior in problems of sexual violence in children and adolescents - Jati, Sri Nugroho; Trisnawati, Elly; Kurniati, Tuti (Universitas Mercu Buana Yogyakarta, 2023)
Family is the smallest unit in society that significantly contributes to protecting family members, one of which is protecting and preventing sexual violence against children and adolescents. The family intervention model (FIM) is a family-based intervention model through efforts to change cognitive, affective, and behavioral aspects. This model seeks to impart knowledge and change parents' behavior concerning the issue of sexual violence in children and adolescents through the application of the family intervention model. This research used a quasi-experimental mixed-method with both quantitative and qualitative approaches. This study found that the paired sample t-test statistically showed that family intervention model contributed to changes in parental behavior toward sexual violence (p-value = 0.000). The results of the regression analysis showed that the family intervention model helped bring bout changes in family behavior toward sexual violence in children and adolescents, by 64%. It is importance to improve the role of parents in increasing communication and assertiveness within the family as a preventive measure against sexual violence.